Avaliação do carboidrato-125 como marcador funcional e de prognóstico em pacientes com cardiopatia chagásica crônica - Angela Braga Rodrigues (2013)
Chagas disease was described in 1909 and after one century it still plagues humanity. There are around10 million infected individuals in the whole world but mainly in Latin America (WHO 2010). In Brazil, chronic cases are mainly due to vetorial transmission. Nowadays Chagas disease has become a worldwide problem due to migration of people to North America and Europe. 30% of infected individuals have or will have some form of cardiac manifestation and 15% show or will show systolic dysfunction which it the most severe manifestation. Chagas cardiomyophaty(CCC) does not seem to be different from other forms of cardiopathies such as ischemic or dilated, in regard to a complex patophisiological mechanism with hemodynamic, neurohormonal and inflammatory alterations. Recently it has been shown an association of tumor marker antigen carbohidrat-125(Ca-125) and acute or chronic heart failure (HF) of diverse etiologies. In a prospective study we have followed 50 patients with CCC in a reference Chagas Disease outpatient clinic from our University Hospital. We have aimed to evaluate Ca-125 as a functional and prognostic marker in patients with CCC. We have found an association of Ca-125 and severity markers such as reduced left ventricular ejection fraction and right ventricular dilation on echocardiogram and also with serum levels of brain natriuretic peptide (BNP). Patients that died and the ones that were hospitalized due to HF had higher Ca-125 serum levels. Ca-125 determination could be useful in the clinical evaluation of these patients, helping to identify those with higher risk of chronic progressively deterioration.